2016
DOI: 10.14814/phy2.12708
|View full text |Cite
|
Sign up to set email alerts
|

Similar degrees of obesity induced by diet or aging cause strikingly different immunologic and metabolic outcomes

Abstract: In obesity, adipose tissue (AT) and liver are infiltrated with Th‐1 polarized immune cells, which are proposed to play an important role in the pathogenesis of the metabolic abnormalities of obesity. Aging is also associated with increased adiposity, but the effects of this increase on inflammation and associated metabolic dysfunction are poorly understood. To address this issue, we assessed insulin resistance (IR) and AT and liver immunophenotype in aged, lean (AL) and aged, obese (AO) mice, all of whom were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…; Krishna et al. ), despite this, species widespread use as a preclinical model of metabolic disease. Further, to the best of our knowledge, no information exists regarding the effect of sex on age‐related obesity and insulin resistance in mice.…”
Section: Introductionmentioning
confidence: 99%
“…; Krishna et al. ), despite this, species widespread use as a preclinical model of metabolic disease. Further, to the best of our knowledge, no information exists regarding the effect of sex on age‐related obesity and insulin resistance in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aging-induced accumulation of islet T cells is not recapitulated by a similar degree of weight gain in diet-induced obese mice, and thus is not driven by obesity. This parallels the divergent immune cell profiles in adipose tissue of aged versus obese mice (31). Similarly, the metabolic outcomes of aging and diet-induced obesity in mice are different, with aging resulting in increased insulin secretion and ultimately improved glucose tolerance in advanced age mice, whereas diet-induced obesity impairs insulin secretion and glucose tolerance.…”
Section: Discussionmentioning
confidence: 85%
“…Aging is also associated with inflammation in adipose tissue promoting insulin resistance, though the changes are distinct from those of obesity. T cells accumulate in aged visceral adipose tissue whereas the total number of macrophages is relatively unperturbed (21,(29)(30)(31), and unlike in diet-induced obesity, adipose tissue T regulatory cells accumulate and contribute to worsening glucose homeostasis during aging (21,29). B2 cells also accumulate in WAT with age, and contribute to insulin resistance and glucose intolerance (32).…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al () recruited 793 women and 1091 men aged 20–40 years and concluded that age influences the body fat mass and other anthropometric indices. Furthermore, aging influences the whole organism, such as gastric emptying, intestinal absorption and metabolism (Krishna, Stefanovic‐Racic, Dedousis, Sipula, & O'Doherty, ; Santos, ), so age may have influenced the findings.…”
Section: Discussionmentioning
confidence: 99%